Management of osteoporosis and Paget's disease. An appraisal of the risks and benefits of drug treatment - Gennari, C; Nuti, R; Agnusdei, D; Camporeale, A; Martini, G (Drug safety, 1994)
Osteoporosis is a major public health problem occurring primarily among the postmenopausal population. Osteoporosis is a preventable disease, but despite several advances in its prevention, treatment of the established disease to date remains a major challenge to be managed by primary care physicians. Stabilisation of bone mass and prevention of falls are of paramount importance in any therapeutic programme for osteoporotic patients with established vertebral fractures. Drug therapy for osteoporosis can be divided operationally into 2 main categories: those that inhibit bone resorption, and thus reduce bone turnover, and those that stimulate bone formation, exerting an anabolic effect. Therapeutic agents that inhibit bone remodeling would appear to be best suited to those patients with high turnover osteoporosis (about 30%). Included in this category are calcium, vitamin D and its metabolites, gonadal steroids, calcitonin, ipriflavone and bisphosphonates. Although estrogen replacement therapy has been proven to be effective in older females, calcitonin appears to be the treatment of choice for this population since it stabilises or increases bone mass and also has reported analgesic properties. Drugs that stimulate bone remodeling or bone formation would be best suited to patients with low turnover osteoporosis (about 70%). The agent in this class that is widely used is sodium fluoride. New therapies include intermittent injections of synthetic parathyroid hormone, and cyclic bisphosphonates to activate then depress resorption and formation. Any attempts to stabilise the skeleton with any drug regimen must be accompanied by an adequate calcium supply, i.e. 1200 to 1500 mg/day). The theoretical basis of tailoring treatment for osteoporosis to the underlying histology has not yet been fully proven, but there is increasing experimental support to this approach. Drugs that inhibit bone turnover, such as calcitonin, appear to be effective in increasing bone mass for 1.5 to 2 years, about the time it would take to replenish the remodeling space in a patient with high turnover osteoporosis. In contrast, although bone mass appears to increase for as long as 5 years in patients treated with sodium fluoride, there has been no consistent reduction in occurrence of vertebral or hip fractures. Paget' disease of bone is a focal disorder of the skeleton characterised by excessive resorption and subsequently disorganised formation of bone. The aetiology of the disease is unknown. Paget's disease may be mono-ostotic or polyostotic; pain and bone deformities due to enlargement of skeletal segments represent the main clinical aspects. However, in many patients the disease may be asymptomatic.